Demographic Factors and BMI on Declined Lung Function and Vitamin D Levels in Active Smokers - Laksono, Pandu; Lorensia, Amelia; Wijono, Heru (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Cigarettes are one of the causes of health problems in the world. Smoking has been known to have a direct impact on reducing lung function. Smoking increases the risk of vitamin D deficiency. Vitamin D is a vital nutrient as a lung immunomodulator. Deficient levels will cause problems with lung health, especially in active smokers. This cross-sectional research using multivariate path analysis and the SEM-PLS method has three objectives. The direct influence of three independent variables, including obesity, smoking, and demographics. Regarding vitamin D status and lung function, analyzing the direct effect of vitamin D on lung function, and thirdly, analyzing the indirect one of the three independent variables on lung function through vitamin D levels. This research took time from October 2023 to January 2024 and involved 47 active smoker respondents whose vitamin D level status and lung function were measured. There was a significant direct effect of obesity level on vitamin D levels in the active smoker population (p<0.05;f-square=2.889). While demographic factors (p>0.05;f-square=0.030) and smoking frequency (p>0.05;f-square=0.003) did not have a direct significant effect. Demographic factors, obesity, and smoking frequency don’t have significant direct effect on lung function in active smokers (p>0.05).